Cultivating Perspective: A Qualitative Inquiry Examining School History Textbooks for Microaggressions against Native Americans. Issue 3 (2nd July 2020) - Holter, Olivia G.; Goforth, Anisa N.; Pyke, Kristen; Shindorf, Zachary R.
ABSTRACT: Native American youth face a number of challenges that affect their academic success and wellbeing. In schools, Native American youth are presented with textbooks that include stereotyped and distorted information about their peoples' history. However, there is a gap in the literature showing whether these textbooks contain microaggressive statements. The current study is a qualitative inquiry into five Montana history that explores the following questions: The first, are there microaggressions in history textbooks used across Montana, and the second – if there are microaggressions, what are those themes? Results of this study indicate that these books included 96 microinvalidations, 54 microinsults, and 11 microassaults. The themes of these microaggressive statements expanded beyond Sanchez's (2007) original themes. In turn, this study discusses the results from a perspective of White privilege, and how educational consultants can help combat this prejudice engrained in curriculum.